Analisis Kinerja Aparat Desa Bottopenno Kecamatan Majauleng Kabupaten Wajo - Eka Patmasari; Darwis Darwis; Meisi Ulfiani R (Konstitusi : Jurnal Hukum, Administrasi Publik, dan Ilmu Komunikasi, 2025)
This study aims to examine and analyze the performance of employees at the Village Office of Bottopenno, Majauleng District, Wajo Regency. The research employed a descriptive analysis method with a total population and sample of 27 employees, all of whom were designated as respondents. Data collection techniques included observation, documentation, and questionnaires distributed to the employees. The collected data were then analyzed using quantitative descriptive analysis to provide a clear picture of employee performance conditions. The findings indicate that employees at the Bottopenno Village Office are able to position and apply their abilities effectively in carrying out the tasks assigned by their superiors. Employees not only complete tasks according to instructions but also demonstrate a high sense of responsibility in handling every duty. This is reflected in the alignment between the work targets set and the outcomes achieved. The performance of employees also meets expectations in terms of discipline, timeliness, and the quality of public services provided. Overall, the performance of the Bottopenno Village Office employees can be categorized as very good. Their work results are in line with the expectations of their superiors and with established regulations, thereby fostering a conducive work environment and ensuring optimal public services. Consequently, the performance of village officials has been running effectively and is expected to continue improving to support the achievement of sustainable village governance goals.